2018
DOI: 10.1128/aem.01263-18
|View full text |Cite
|
Sign up to set email alerts
|

A Linear Plasmid-Like Prophage of Actinomyces odontolyticus Promotes Biofilm Assembly

Abstract: The human oral cavity is home to a large number of bacteria and bacteriophages (phages). However, the biology of oral phages as members of the human microbiome is not well understood. Recently, we isolated subsp. strain XH001 from the human oral cavity, and genomic analysis revealed the presence of an intact prophage named xhp1. Here, we demonstrated that xhp1 is a linear plasmid-like prophage, which is a newly identified phage of The prophage xhp1 genome is a 35-kb linear double-stranded DNA with 10-bp single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Actinomyces odontolyticus, core microbiome of the healthy community with relative abundance > 1%, is a gram-positive facultative aerobic bacterium, which decreased significantly in the HD community. Previous studies have reported that A. odontolyticus was the host of the candidate phylum Saccharibacteria, being associated with human inflammatory mucosal diseases, thereby killed by a parasitic phase [51,52]. By contrast, Porphyromonas gingivalis, core microbiome of the HD community with relative abundance > 1%, is a convincedly proposed keystone bacterium in the genesis and development of periodontitis, which was at significantly higher level in the HD group.…”
Section: Discussionmentioning
confidence: 84%
“…Actinomyces odontolyticus, core microbiome of the healthy community with relative abundance > 1%, is a gram-positive facultative aerobic bacterium, which decreased significantly in the HD community. Previous studies have reported that A. odontolyticus was the host of the candidate phylum Saccharibacteria, being associated with human inflammatory mucosal diseases, thereby killed by a parasitic phase [51,52]. By contrast, Porphyromonas gingivalis, core microbiome of the HD community with relative abundance > 1%, is a convincedly proposed keystone bacterium in the genesis and development of periodontitis, which was at significantly higher level in the HD group.…”
Section: Discussionmentioning
confidence: 84%
“…To add to this complexity, viruses has been shown to promote biofilm formation for a number of bacterial genera, such as Bacillus and Actinomyces, via spontaneous induction of prophage and release of extracellular DNA, which contributes to the extracellular matrix (Schuch and Fischetti, 2009;Carrolo et al, 2010;Wang et al, 2010;Shen et al, 2018). Davies et al (2016) have also demonstrated that temperate viruses can drive the evolution and adaptation of cells within a biofilm through insertional inactivation of genes.…”
Section: Biofilm Formation and Virus: Biofilm Interactionsmentioning
confidence: 99%
“…These findings suggest that temperate phages play some role in bacterial biofilms. Laboratory-scale studies with single species biofilms suggests that prophage induction is an important process in the release of extracellular DNA, a necessary component of the biofilm matrix [ [54] , [55] , [56] ]. Thus, prophage induction may likewise be an important mechanism for building the biofilm matrix in mixed species lotic biofilms.…”
Section: Discussionmentioning
confidence: 99%